2008
DOI: 10.1089/cpb.2007.0016
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying among Turkish Adolescents

Abstract: Cyberbullying, harassment through the use of information and communication technology such as cell phones and the Internet, is an emerging phenomenon all around the world. Extensive research on aggression and bullying is guiding educators' understanding of cyberbullying. Yet the gap between the advancement in technology and the dearth of study on cyberbullying suggests that more research is needed to understand the scope of this form of bullying. In order to fill the gap in literature, 269 secondary school Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
193
1
29

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(242 citation statements)
references
References 36 publications
19
193
1
29
Order By: Relevance
“…Technical solutions can include avoidant coping behaviors such as changing the username or account ID, changing email address or phone number, unfriending on social media, and/or blocking messages or users (Aricak et al, 2008;Juvonen & Gross, 2008;Smith et al, 2008). Juvonen and Gross (2008) reported that 67% of participants in a US sample had blocked someone, 33% had removed the person from their friends list on the website, and 26% had changed their username or email.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Technical solutions can include avoidant coping behaviors such as changing the username or account ID, changing email address or phone number, unfriending on social media, and/or blocking messages or users (Aricak et al, 2008;Juvonen & Gross, 2008;Smith et al, 2008). Juvonen and Gross (2008) reported that 67% of participants in a US sample had blocked someone, 33% had removed the person from their friends list on the website, and 26% had changed their username or email.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…For instance, spreading rumors (7.8 %) on the internet were found to be common in this research. Arıcak et al (2008) found that spreading rumors (14.7 %) was more common among secondary school students. In contrary, Çetinkaya (2010) found that spreading rumors (2.9 %) was not very common.…”
Section: Discussionmentioning
confidence: 97%
“…Arıcak et al (2008) also found that saying things online that would not be said face to face was the most common cyber bullying behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Turkish study, unwanted phone calls, text messages or comments on the phone, or on the internet were reported to be the most common forms of cyber aggression among the young adolescents (Yurtal & Cenkseven, 2016). In another study, 23.8% of young adolescents reported themselves to be both perpetrators and victims of cyber aggression, 35.7% were perpetrators only, and 5.9% victims only (Aricak et al, 2008). Yilmaz (2011) found that 17.9% of the responding young adolescents reported victimization from cyber aggression, and 6.4% of them reported perpetration of cyber aggression, with 'posting mean or hurtful comments online' being the most common form of cyber aggression.…”
Section: Introductionmentioning
confidence: 97%